Visualization of membrane protein crystals in lipid cubic phase using X‐ray imaging. (21st June 2013) - Warren, Anna J.; Armour, Wes; Axford, Danny; Basham, Mark; Connolley, Thomas; Hall, David R.; Horrell, Sam; McAuley, Katherine E.; Mykhaylyk, Vitaliy; Wagner, Armin; Evans, Gwyndaf
Abstract : The focus in macromolecular crystallography is moving towards even more challenging target proteins that often crystallize on much smaller scales and are frequently mounted in opaque or highly refractive materials. It is therefore essential that X‐ray beamline technology develops in parallel to accommodate such difficult samples. In this paper, the use of X‐ray microradiography and microtomography is reported as a tool for crystal visualization, location and characterization on the macromolecular crystallography beamlines at the Diamond Light Source. The technique is particularly useful for microcrystals and for crystals mounted in opaque materials such as lipid cubic phase. X‐ray diffraction raster scanning can be used in combination with radiography to allow informed decision‐making at the beamline prior to diffraction data collection. It is demonstrated that the X‐ray dose required for a full tomography measurement is similar to that for a diffraction grid‐scan, but for sample location and shape estimation alone just a few radiographic projections may be required.